Electronic Materials / Inside Electronic Devises - Braithwaite Nicholas; Weaver Graham (Butterworth Heinemann, 1998)
The book explains the scientific models needed to guide those manipulations and describes how they are commercially exploited inside electronic devices. Goals and Gambits, Materials and Circuits, Something about Magnets, Transducers, Memory Microtechnology, Displays, Warm Superconductor - So What?, Optoelectronics, In Perspective, Acknowledgements, Index of Materials, Subject Index.